2016
DOI: 10.12669/pjms.326.11511
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of B7-H3 expression in patients with colorectal cancer: A meta-analysis

Abstract: Objective:The co-stimulatory molecule B7-H3 plays an important role in prognosis of several malignancies. However, its prognostic value in clinic in patient with colorectal cancer (CRC) is still controversial. This meta-analysis evaluated the relationship between B7-H3 expression and the outcomes of CRC patients.Methods:PubMed, Google Scholar, Embase, CNKI and Wanfang database were searched for the studies on the relationship between the expression of B7-H3 and prognosis of CRC patients. Pooled odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…B7-H3, as one of the crucial immune checkpoint proteins, plays a critical role in the occurrence and development of CRC. Clinically, the expression of B7-H3 was associated with unfavorable outcomes in CRC patients (12,26). However, there was no relationship between B7-H3 expression and OS in this study, which might be attributed to low sample size or the uncertainty of repeated experiments.…”
Section: Discussioncontrasting
confidence: 61%
“…B7-H3, as one of the crucial immune checkpoint proteins, plays a critical role in the occurrence and development of CRC. Clinically, the expression of B7-H3 was associated with unfavorable outcomes in CRC patients (12,26). However, there was no relationship between B7-H3 expression and OS in this study, which might be attributed to low sample size or the uncertainty of repeated experiments.…”
Section: Discussioncontrasting
confidence: 61%
“…B7-H3 expression is significantly associated with poor outcome in patients with RCC (2830), lung cancer (31), prostate cancer (32), CRC (33, 34), gallbladder cancer (35), esophageal squamous cancer (36), cervical cancer (37), osteosarcoma (OS) (38) and breast cancer (39). Thus, B7-H3 expression might be a feasible and effective means to predict the prognosis in cancer patients.…”
Section: B7-h3mentioning
confidence: 99%
“…A study using tissue microarray analysis in CRC demonstrated that B7-H3 expression was correlated with clinical pathology and patient outcomes (23). Similarly, a meta-analysis including 1,202 total CRC cases showed that B7-H3 in CRC patients was obviously related to 24-and 72month OS (25), demonstrating that CRC patients overexpressing B7-H3 may have a poor survival rate. In addition, nuclear localization of B7-H3 (23) and aberrant expression of B7-H3 in CD133 + CRC cells (26) were found to be closely associated with tumor progression and strongly predicted poor outcomes in CRC.…”
Section: B7 Homologmentioning
confidence: 99%